Comparative Analysis of Pediatric Deep Neck Infection Management: A Systematic Review Comparing Conventional Medical Treatment and Surgical Intervention - Khoirul Anam; Andre Niljon; Faishal Arief; Luthfi Ariwibiwo (International Journal of Health and Pharmaceutical (IJHP), 2026)
Background : Pediatric deep neck infections (DNI), including abscesses, constitute a serious clinical challenge due to their rapid progression and the risk of severe complications such as airway obstruction and sepsis. These infections are generally bacterial in origin and often arise from common ailments like tonsillitis or pharyngitis, spreading deeper into the neck area. The management of DNI involves two main approaches: medical therapy using antibiotics or surgical intervention to drain abscesses. However, selecting the most effective approach, whether medical or surgical, requires careful consideration, particularly concerning the patient’s age, infection severity, and potential side effects. This study aims to provide a comparative analysis of both methods to assist clinicians in choosing the best approach for managing DNIs in children, thereby minimizing risks and achieving optimal recovery. Methods : This research used the Systematic Literature Review (SLR) method with guidance from the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). PRISMA stages included the identification of relevant articles through databases such as PubMed, Google Scholar, and ScienceDirect using keywords "medical management" and "surgical management" for pediatric deep neck abscesses. Inclusion criteria encompassed English-language journals published between 2015 and 2022, focusing on studies that compared the effectiveness of antibiotic therapy and surgical interventions in pediatric deep neck abscesses. Identified articles were screened to eliminate duplicates and ensure compliance with inclusion criteria. The qualifying articles were then thoroughly evaluated, and relevant data were extracted, including study design, sample size, main outcomes, as well as complications and recovery rates associated with both methods. This approach was intended to provide an objective and comprehensive understanding of the efficacy of medical and surgical therapies in pediatric deep neck abscess cases. Results : The study revealed that the medical approach using antibiotics is effective for mild to moderate pediatric deep neck infections (DNI), particularly in small, uncomplicated abscesses. However, for larger abscesses or those with significant complications, surgical intervention yields better outcomes in controlling the infection and expediting recovery. Additionally, the use of dexamethasone in the medical approach can reduce the need for surgical intervention in some cases. A combination of antibiotic therapy and stringent monitoring proves appropriate for moderate cases, whereas early surgery is more advisable for cases exhibiting clinical instability or widespread infection. Conclusion: The management of pediatric deep neck infections should be individualized according to infection severity and clinical presentation. Medical treatment with intravenous antibiotics is effective for mild to moderate cases, particularly in small and uncomplicated abscesses, while surgical intervention is recommended for larger abscesses, clinical instability, or extensive infection. The adjunctive use of dexamethasone may reduce the need for surgery in selected patients. Therefore, an appropriate treatment strategy combining medical therapy, close monitoring, and timely surgical intervention can optimize clinical outcomes and minimize complications in pediatric DNI.